Myanmar's China policy shift: preparing for ASEAN chair? - Yang Razali Kassim (2016)
As Myanmar prepares to take over the ASEAN Chair in 2014, it appears to be rebalancing its ties with China. What lies behind this shift and what does it mean for ASEAN?